Seroprevalence of Transfusion-Transmissible Infections among Blood Donors: Seroprevalensi Infeksi Menular Lewat Transfusi Darah pada Pendonor - Hartalina Mufidah; Dhika Juliana Sukmana (Universitas Muhammadiyah Sidoarjo, 2026)
Transfusion-Transmitted Infections (TTIs) is one of the crucial health problem of blood transfusions. In Jember Regency the number of HIV cases reported is relatively high. Meanwhile, data on the prevalence of cases of Hepatitis B, Hepatitis C and Syphilis is still lacking in Jember Regency. The aim of this study was to determine the prevalence, relationship and Prevalence Odds Ratio between variable age, gender, and donor status and the TTIs i.e HBsAg, HCV, HIV, syphilis. This study design is a cross-sectional. This study took secondary data of TTIs at the UDD PMI in Jember Regency from January to December 2019. The sampling technique was used total sampling, and 559 data were recorded. The data analysis used was univariate and chi-square, using SPSS version 20.0 software. The result of this study showed that the difference between age group and sex had p-value >0,05 with TTIs. Based on donor status, the difference between donor status had p-value <0,05 with TTIs. It can be conclude that the seroprevalence of TTIs at at the Blood Donor Unit Indonesian Red Cross in Jember Regency of HBsAg are 39.9%, HCV 65.1%, HIV 65.1%, and syphilis 59.2%. There is no relathioship between age and sex with TTIs and there is relathionship between donor status with TTIs. Prevalence Odds Ratio of HBsAg are 0.5 times, HCV are 1.8 times, HIV are 1.8 times, and syphilis 1,6 times more likely to be detected in repeat donors than in first-time donors.